2012
DOI: 10.1364/josaa.29.00a268
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, color vision deficiencies, and blood oxygen saturation

Abstract: Chromatic thresholds were measured using the Cambridge Colour Test (CCT), the Colour Assessment and Diagnosis (CAD) test, and the Cone Specific Contrast Test (CSCT) at ground and 3780 m (12,400 ft) for subjects with normal color vision and red-green color vision defects. The CAD revealed a small (~10%) increase in the red-green thresholds for the trichromatic subjects and a similar increase in the blue-yellow thresholds for the dichromats. The other two color vision tests did not reveal any significant change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
2
8
0
2
Order By: Relevance
“…For instance, among the two photoreceptors (rods and cones) present in the retina of adult zebrafish, larval stages (until 15–40 dpf; Billota and Saszik, 2001 ) only have developed cones, which are responsible for colour vision. Cones would be more sensitive to metabolically related oxygen deficiencies, which is consistent with earlier studies on hypoxia and colour vision capabilities in humans, indicating that hypoxia could impair colour vision ( Vingrys and Garner, 1987 ; Barbur and Connolly, 2011 ; Hovis et al, 2012 ). The visual neural circuits in the zebrafish larval brain undergo dynamic formation during its early ontogenesis ( Dunn et al, 2016 ) and temperature also influences neuronal circuits functioning by inducing various physiological processes, such as compensation, tuning and tolerance, making it difficult to precisely predict the overall influence on the output ( Robertson and Money, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, among the two photoreceptors (rods and cones) present in the retina of adult zebrafish, larval stages (until 15–40 dpf; Billota and Saszik, 2001 ) only have developed cones, which are responsible for colour vision. Cones would be more sensitive to metabolically related oxygen deficiencies, which is consistent with earlier studies on hypoxia and colour vision capabilities in humans, indicating that hypoxia could impair colour vision ( Vingrys and Garner, 1987 ; Barbur and Connolly, 2011 ; Hovis et al, 2012 ). The visual neural circuits in the zebrafish larval brain undergo dynamic formation during its early ontogenesis ( Dunn et al, 2016 ) and temperature also influences neuronal circuits functioning by inducing various physiological processes, such as compensation, tuning and tolerance, making it difficult to precisely predict the overall influence on the output ( Robertson and Money, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings show that EWM lesions that disrupt parasympathetic control of ChBF adversely affect short wavelength-sensitive blue/violet cones and principal cones, and this effect is exacerbated by CL. These photoreceptor types have been shown in prior studies in mammals and birds to be preferentially vulnerable as well to light, hypoxia, and aging (Greenstein et al, 1989 ; Hodos et al, 1991 ; Fite et al, 1993 ; Machida, 1994 ; Curcio, 2001 ; Algvere et al, 2006 ; Organisciak & Vaughn, 2010 ; Hovis et al, 2012 ). Our results and their implications are discussed in more detail below.…”
Section: Discussionmentioning
confidence: 81%
“…Prior studies have also found these to be among the most vulnerable of the photoreceptor cell types. For example, short wavelength cones in diurnal species, including avian species, have been reported to be vulnerable to: (1) constant or bright light (Sperling et al, 1980 ; Sykes et al, 1981 ; Sperling, 1986 ; Machida, 1994 ); (2) hypoxia (Smith et al, 1976 ; Algvere et al, 2006 ; Connolly et al, 2008 ; Hovis et al, 2012 ); and (3) aging (Eisner et al, 1986 ; Haegerstrom-Portnoy, 1988 ; Gao & Hollyfield, 1992 ; Curcio et al, 1993 ; Gray et al, 1995 ; Algvere et al, 2006 ; Okano et al, 2012 ). Blue cone vulnerability and loss in humans have also been observed in diabetic retinopathy, glaucoma, and retinitis pigmentosa (Greenstein et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores têm encontrado perdas generalizadas na discriminação cromática sob essas condições (Vingrys e Garner, 1987;Hovis, Milburn, e Nesthus, 2012), mas estas são normalizadas após o retorno a baixas altitudes (Willmann et al, 2010). Gualieri, M. (2008) Este termo de consentimento está sendo emitido em duas vias de igual teor, uma cópia será dada a você (ou seu responsável), e outra que ficará com o pesquisador.…”
Section: Resultsunclassified